Perancangan Sistem Pendukung Keputusan Pemilihan Aparat Desa Kebirangga Selatan Menggunakan Metode Simple Additive Weighting (Saw) - Longinus Bei; Ferdinandus Lidang Witi; L.B.Finansius Mando (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Village apparatus is something important in the village for service to the community. Currently in South Kebirangga Village, the selection of Village Apparatus Candidates is still manual, so services to the community will be hampered. Until now, there is no effective system for selecting Village Apparatus Candidates for the selection of Village Apparatus candidates in South Kebirangga, the method of selecting and determining who will qualify and occupy the position of village apparatus is less effective. This study aims to assist the village in the Selection of Candidates for the Village Apparatus of South Kebirangga. This system is built using the SAW method so that the programmed system can be carried out more effectively. The SAW method is one of the methods used in decision support systems with a calculation process by finding the weight value or suitability rating for each attribute. Keywords: Decision Support System, Simple Additive Weighting (SAW), Village Apparatus.